Practical Webix Learn to Expedite and Improve your Web Development - Zammetti, Frank (Apress, 2018)
Learn to create speedy cross-platform applications with ease using Webix. You will begin with an introduction to Webix and basic usage, exploring the interface components and utilities it offers, as well as the tools available (skin builder, form builder, and code snippet testing facility). You'll understand how Webix can integrate with other popular libraries and frameworks including Angular, Vue, React and more (as well as third-party components like dHTMLx and rich text editors). You will learn tangential topics including communication with back-end systems (Node.js and common related tooling), packaging as a Cordova app and, of course, you will learn how to use Webix following the Progressive Web App delivery mechanism. Offering a complete solution in a single bundle, this JavaScript UI framework provides a rich set of interface components, application architecture direction, and commonly-needed utility and ancillary capabilities. Every topic will be taught a practical way, explored within the context of building real-world working apps, not through unrelated snippets. Bringing 25 years of professional development experience to the table, author Frank Zammetti uses his unique levity to teach you how to get up and running with this new and upcoming framework. .